Blockchain-based cryptography model to preserve privacy for smart contracts. (17th November 2021) - Priyanka,; Keswani, Bright; Hussain, Rashid
Abstract: As a computer programmer, a smart contract encapsulates the contractual features of the parties' transactions through code. Some blockchain technology platforms, such as Hyperledger Fabric, IBM Blockchain and Ethereum, currently allow smart contracts. Smart contracts on these platforms are kept on the blockchain and are not under the control of any party involved. They can't be tampered with after they've been digitally signed and placed on the blockchain. The use of smart contracts in blockchains is critical. It is the authors' primary goal with this research to provide an alternative to standard contracts by allowing users to modify data stored in the chain. Methodology for designing smart contracts is presented in this article, along with an example of how it has used modifications to the data stored in the chain. In this article, we present a methodology for the design of smart contracts and we also illustrate its application with a case study.